Types and productivity of indigenous African small ruminants - Wilson, R.T. (Small Ruminant Collaborative Research Support Program, 1984)
Discusses types & productivity of indigenous African small ruminants. Presents data on varieties & productivity of sheep & goat in semi-arid Africa and in different countries, management objectives related to sheep flock structures, weight for age for intensively fed compared with range fed sheep in West Africa. Shows with diagram the potential improvement pathways for sheep and goat flocks on major group ranches. Discusses the system of productivity indices ILCA is using.